Formulation and Evaluation of Colon Targeted Compression Coated Tablet of Mesalamine and Prednisolone for Ulcerative Colitis (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: The purpose of this study was to formulate compression coated tablets of mesalamine and prednisolone for colon specific delivery and evaluate their in vitro and in vivo performances. Materials and Methods: Mesalamine is 5-amino salicylic acid used as a topical anti-inflammatory agent and prednisolone is a synthetic glucocorticoid used for the treatment of various types of inflammatory and autoimmune conditions. Pectin was used as an enzyme dependent polymer. Eudragit S 100 was used to enteric coat the compression coated tablets to avoid prerelease of the drug into the upper gastrointestinal tract. In vitro release study was carried out at various pH (1.2, 6.8 and 7.4) and in the presence of the pectinolytic enzyme. Therapeutic efficacy of the prepared tablets was evaluated in trinitrobenzene sulfonic acid-induced rabbit colitis model. Results: Formulation CF3c which was compression coated with of 150% of pectin and enteric coated with 7.5% Eudragit S 100 released 35.86% of mesalamine and 45.49% of prednisolone at the end of 7 h. The release increased significantly to 73.53% of mesalamine and 87.53% of prednisolone on addition of pectinolytic enzyme to the dissolution medium at the end of 10 h. Formula CF3c significantly reduced the inflammation of the treated group and the myeloperoxidase activity to 3.91 U/g. Conclusion: Studies demonstrated that orally administered compression coated tablets could be used effectively for the delivery of the drug to the colon.